Vancomycin-resistant Enterococcus faecium: admission prevalence, sequence types and risk factors–a cross-sectional study in seven German university hospitals from 2014 to 2018. (April 2023) - Rohde, Anna M.; Walker, Sarah; Behnke, Michael; Eisenbeis, Simone; Falgenhauer, Linda; Falgenhauer, Jane C.; Häcker, Georg; Hölzl, Florian; Imirzalioglu, Can; Käding, Nadja; Kern, Winfried V.; Kola, Axel; et al.
Abstract: Objectives: Assessment of vancomycin-resistant Enterococcus faecium (VREfm) prevalence upon hospital admission and analysis of risk factors for colonization. Methods: From 2014 to 2018, patients were recruited within 72 hours of admission to seven participating German university hospitals, screened for VREfm and questioned for potential risk factors (prior multidrug-resistant organism detection, current/prior antibiotic consumption, prior hospital, rehabilitation or long-term care facility stay, international travel, animal contact and proton pump inhibitor [PPI]/antacid therapy). Genotype analysis was done using cgMLST typing. Multivariable analysis was performed. Results: In 5 years, 265 of 17, 349 included patients were colonized with VREfm (a prevalence of 1.5%). Risk factors for VREfm colonization were age (adjusted OR [aOR], 1.02; 95% CI, 1.01–1.03), previous (aOR, 2.71; 95% CI, 1.87–3.92) or current (aOR, 2.91; 95% CI, 2.60–3.24) antibiotic treatment, prior multidrug-resistant organism detection (aOR, 2.83; 95% CI, 2.21–3.63), prior stay in a long-term care facility (aOR, 2.19; 95% CI, 1.62–2.97), prior stay in a hospital (aOR, 2.91; 95% CI, 2.05–4.13) and prior consumption of PPI/antacids (aOR, 1.29; 95% CI, 1.18–1.41). Overall, the VREfm admission prevalence increased by 33% each year and 2% each year of life. 250 of 265 isolates were genotyped and 141 (53.2%) of the VREfm were the emerging ST117. Multivariable analysis showed that ST117 and non-ST117 VREfm colonized patients differed with respect to admission year and prior multidrug-resistant organism detection. Discussion: Age, healthcare contacts and antibiotic and PPI/antacid consumption increase the individual risk of VREfm colonization. The VREfm admission prevalence increase in Germany is mainly driven by the emergence of ST117.